Brain volumetric analysis of elderly patients based on hearing levels quantified using FreeSurfer - Lee, Yun Ji; Lee, Eun-Jae; Suh, Chong Hyun; Youn, Hye Jung; Chae, Jihye; Park, Keunwoo; Kweon, Jihoon; Ahn, Joong Ho (Frontiers in Neurology, 2025)
ObjectiveThis study investigated the effects of hearing loss on brain volume, particularly total gray matter, the cerebellum, and the limbic system, using MRI data analyzed with FreeSurfer software.Study DesignData was obtained from 745 individuals aged 60 or older who underwent health screenings at Asan Medical Center between March and December 2019. Participants were categorized into three groups based on their pure-tone hearing thresholds: normal hearing (<20 dB, n = 328), mild hearing loss (20–40 dB, n = 336), and moderate-to-severe hearing loss (≥40 dB, n = 81).ResultsResults showed significant differences among the groups in age, sex, and health conditions such as hypertension, diabetes, and cholesterol levels (p < 0.05). Increased hearing loss severity correlated with older age, male predominance, and higher prevalence of these conditions. Multiple regression analysis, controlling for confounders like age and comorbidities, revealed age-related brain atrophy across all groups. Notably, even mild hearing loss was associated with reduced total gray matter volume, while moderate-to-severe hearing loss led to significant hippocampal volume reduction.ConclusionThe findings suggest that hearing loss in individuals over the age of 60 may contribute to the atrophy of critical brain regions, particularly the hippocampus and total gray matter. The study emphasizes the importance of addressing even mild hearing loss, as active hearing rehabilitation could potentially prevent cortical volume loss and mitigate the risk of cognitive decline.